IMPLEMENTASI PENILAIAN RISIKO DALAM MENUNJANG PENCAPAIAN TUJUAN INSTANSI PENDIDIKAN - Andian Ari Istiningrum (Jurnal Pendidikan Akuntansi Indonesia, 2011)
This study is conducted in order to provide information for heads of the educationinstitution to anticipate the risks faced by their institutions. It is necessary for educationinstitutions to do risk assessment since the institutions will always face significant changesthat occur due to internal and external changes. The step of risk assessment starts from settingthe institution objectives. It is important to divide the institution objectives into more specificone by formulating the objectives for every program. The second step of risk assessment isrisk identification. In this step, the risks need to be identified and categorized. In addition,factors that cause the risks should also be analyzed. The last step of risk assessment isanalyzing risk. Here, the institution will try to determine the risk status and risk map so thatappropriate respons could be taken to handle the risks.Kata kunci: penilaian risiko, perumusan tujuan, identifikasi risiko, analisis risiko